Subcluster AZ1 Annotation Report - Beyer, Andrea; Bouklas, Tejas; Dojs, Madeline; Edgington, Nicholas; Harrison, Melinda; Rudner, Adam; Swerdlow, Sarah; Delesalle, Veronique; Page, Shallee (QUBES, 2025)
This report describes features of actinobacteriophages assigned to subcluster AZ1. Additional phages may have been added to the phagesDB database since the generation of this report.
Keywords: Annotation; DNA; Genome; Genomics; Human genome; Selection (genetic algorithm); dept.bio

Tissue-specific I-Smad mechanisms revealed by structure-function analysis in Drosophila - Simoncek, Ania; Sviridoff, Steven; Hays, J.; Graichen, Noah; Sulkowski, Mikolaj (bioRxiv (Cold Spring Harbor Laboratory), 2025)
Abstract Inhibitory Smads (I-Smads) regulate TGF-β/BMP signaling through multiple distinct mechanisms, but whether different tissues preferentially employ specific mechanisms remains unknown. To address this question, we performed structure-function analyses of the Drosophila I-Smad Dad and its vertebrate orthologs Smad6 and Smad7 in neural and wing tissues, measuring in vivo outputs of BMP signaling. We identified a critical 24-amino acid putative DNA-binding domain (DNABD) within the MH1 domain of the Drosophila I-Smad, Dad, that is essential for inhibitory function in wing tissue but unessential in neural tissue. Structural analyses revealed that ΔDNABD disrupts a beta hairpin structure homologous to R-Smad DNA-binding regions. We also found that Dad requires an intact MH1 domain to disrupt wing development, whereas either MH1 or MH2 can independently disrupt BMP signaling in motor neurons. These findings support a model where Dad functions through MH1-mediated transcriptional regulation in wing primordium, but through multiple mechanisms in neurons. Comparative analysis revealed that vertebrate I-Smad orthologs also show tissue-specific activity patterns, with structural predictions suggesting that Smad6 retains ancestral DNA-binding capacity while Smad7 has evolved enhanced MH2-mediated functions. These results reveal context-dependent mechanisms of I-Smads that further the understanding of TGF-β/BMP pathway regulation.
Keywords: Biology; Cell biology; Context (archaeology); Decapentaplegic; Drosophila melanogaster; Function (biology); Gene; Genetics; Primordium; SMAD; Signal transduction; Vertebrate; dept.bio

Comparative genomic analysis of Cluster AZ Arthrobacter phages - Freise, Amanda; Furlong, Kieran; Klyczek, Karen; Beyer, Andréa; Chong, Rebecca; Edgington, Nicholas; Gibb, Bryan; Swerdlow, Sarah; Bendele, Madison; Cobb, Isobel; Mitchell, Zachary; Cresawn, Steven; et al. (bioRxiv (Cold Spring Harbor Laboratory), 2025)
Abstract Bacteria in the Arthrobacter genus belong to the phylum Actinobacteria and are primarily soil-dwelling. Over 600 bacteriophages infecting Arthrobacter hosts have been isolated and sequenced, and genomic analyses show these phages to be highly diverse with mosaic genome architectures. We describe here a group of 32 Arthrobacter phages grouped in Cluster AZ, isolated on four different Arthrobacter strains all with siphoviral morphologies. The Cluster AZ phages exhibit a spectrum of diversity and can be subdivided into four subclusters. The diversity in minor tail protein and endolysin genes correlates partly with isolation host strain and may be predictive of the host range of these phages. Most of the Cluster AZ phages are temperate, form stable lysogens, and encode an integrase; however, an immunity repressor gene has not been identified. The intracluster diversity was analyzed in-depth at the whole genome level and through individual genes. As more Arthrobacter phages are isolated and analyzed they continue to provide new insights into phage evolution.
Keywords: Arthrobacter; Bacteria; Biology; Cluster (spacecraft); Computational biology; Computer science; Genetics; dept.bio

Alternative splicing and parallel patterns of gene expression underlie population and life history divergence in an amphibian - Hu, Juntao; Ren, Xingyue; Barrett, Rowan; Samma, Eman; Sulkowski, Mikloaj; Brady, Steven (2025)
Keywords: Alternative splicing; Amphibian; Biology; Computational biology; Demography; Divergence (linguistics); Ecology; Evolutionary biology; Gene; Gene expression; Genetics; Life history; Messenger RNA; Population; RNA splicing; Sociology; dept.bio

Genomic comparison of the temperate coral Astrangia poculata with tropical corals yields insights into winter quiescence, innate immunity, and sexual reproduction - Stankiewicz, Kathryn; Guiglielmoni, Nadège; Kitchen, Sheila; Flot, Jean‐François; Barott, Katie; Davies, Sarah; Finnerty, John; Grace, Sean; Kaufman, Leslie; Putnam, Hollie; Rotjan, Randi; Sharp, Koty; et al. (G3 Genes Genomes Genetics, 2025)
Facultatively symbiotic corals provide important experimental models to explore the establishment, maintenance, and breakdown of the mutualism between corals and members of the algal family Symbiodiniaceae. Here, we report the de novo chromosome-scale genome assembly and annotation of the facultatively symbiotic, temperate coral Astrangia poculata. Though widespread segmental/tandem duplications of genomic regions were detected, we did not find strong evidence of a whole-genome duplication event. Comparison of the gene arrangement between As. poculata and the tropical coral Acropora millepora revealed considerable conserved colinearity despite ∼415 million years of divergence. Gene families related to sperm hyperactivation and innate immunity, including lectins, were found to contain more genes in Ac. millepora relative to As. poculata. Sperm hyperactivation in Ac. millepora is expected given the extreme requirements of gamete competition during mass spawning events in tropical corals, while lectins are important in the establishment of coral-algal symbiosis. By contrast, gene families involved in sleep promotion, feeding suppression, and circadian sleep/wake cycle processes were expanded in As. poculata. These expanded gene families may play a role in As. poculata's ability to enter a dormancy-like state (winter quiescence) to survive freezing temperatures at the northern edges of the species' range.
Keywords: Biology; Coral; Ecology; Evolutionary biology; Gene; Genetics; Genome; dept.bio

Isolated Abelisaurid Teeth from Gondwana and Dental Evolution in Abelisauridae - Hendrickx, Christophe; Núñez, Matías Soto; Araújo, Ricardo; Meso, Jorge G.; Maganuco, Simone; Ben-Salahuddin, Adé (Ameghiniana, 2025)
Abelisauridae were medium to large-bodied carnivorous dinosaurs with short, ornamented skulls, poorly recurved ziphodont teeth, and reduced forelimbs. They were the dominant terrestrial carnivores in many Gondwanan ecosystems during the Cretaceous. Their Jurassic origin, primarily based on the putative abelisaurid Eoabelisaurus from the Early Jurassic of Patagonia, remains debated, with many authors considering Abelisauridae as a strictly Cretaceous theropod radiation. Here, we describe several historically and stratigraphically important isolated theropod teeth from Gondwana, identified as belonging to abelisaurids using new cladistic and machine learning methods. Dental evolution in Abelisauridae was additionally explored using an updated version of a dentition-based data matrix focused on ceratosaurs. Results of this study show that the evolution of the dentition in abelisaurids was marked by a decrease in size of the mesialmost dentary teeth and the displacement of the tallest crowns towards the middle part of the maxilla. Two isolated abelisaurid teeth from the Late Cretaceous of India and Patagonia were also identified as the earliest published record of a non-avian theropod in Asia and an abelisaurid in Argentina, respectively. More importantly, isolated theropod teeth confidently referred to Abelisauridae from the Middle Jurassic of Madagascar provide additional support for the emergence of this clade in Gondwana before the Late Jurassic and reveal that the acquisition of abelisaurid dental traits occurred early in the evolutionary history of one of the most successful radiations of non-avian theropods from Europe and the Southern Hemisphere. © 2025 Asociación Paleontológica Argentina (APA)
Keywords: Biological evolution; Ceratosauria; Corona; Crown; Dentición; Dentition; Gondwana; Hemisferio Sur; Mandible (arthropod mouthpart); Phylogenetics; Southern Hemisphere; Terópodos; Theropoda; dept.bio

Effects of intraspecies and interspecies competition on genetic device construction and performance - Thompson, Samantha; Williams, Adrian; Dill, Veronica; Marshall, Deven; Sawyer, Emily; Alexander, Mason; Rahn-Lee, Lilah; Shih, Joseph (mSphere, 2025)
ABSTRACT One exciting class of future genetic devices could be those deployed in microbes that join complex microbial environments in the wild. We sought to determine whether genetic parts designed for monoculture are predictable when used in co-culture by testing constitutive Anderson promoters driving the expression of chromoproteins from a plasmid. In Escherichia coli monoculture, a high copy number origin of replication causes stochastic expression regardless of promoter strength, and high constitutive Anderson promoter strength leads to selection for inactivating mutations, resulting in inconsistent chromoprotein expression. Medium- and low-strength constitutive Anderson promoters function more predictably in E. coli monoculture but experience an increase in inactivating mutations when grown in co-culture over many generations with Pseudomonas aeruginosa . Expression from regulated promoters instead of constitutive Anderson promoters can lead to stable expression in a complex wastewater culture. Overall, we show intraspecies selection for inactivating mutations due to a competitive growth advantage for E. coli that do not express the genetic device compared to their peers that retain the functional device. We show additional interspecies selection against the functional device when E. coli is co-cultured with another organism. Together, these two selection pressures create a significant barrier to genetic device function in microbial communities that we overcome by utilizing a regulated E. coli promoter. Future strategies for genetic device design in microorganisms that need to function in a complex microbial environment should focus on regulated promoters and/or strategies that give the microorganism carrying the device a selective or growth advantage. IMPORTANCE First-generation biotechnology focused on genetic devices designed for use in monoculture conditions. One class of next-generation biotechnology devices could be designed to function in complex ecosystems with other organisms, so we sought to create conditions where the genetic device retained function when the organism carrying it is in co-culture with other organisms. We discovered that when the genetic device is a significant resource burden on the organism carrying the device, mutations will be selected for due to intraspecies and interspecies selection pressures, and the device will be rendered non-functional. Therefore, genetic device design for complex ecosystems in next-generation biotechnology needs to balance functionality of the genetic device with the need to reduce resource burden on the organism carrying it.
Keywords: Competition (biology); Function (biology); Genetic diversity; Genetic screen; Model organism; Organism; Resource (disambiguation); Selection (genetic algorithm); chromoproteins; dept.bio; genetics; interspecies selective pressure; microbial communities; promoters

Alternative Splicing and Gene Expression Variation Underlie Population and Life History Differences in an Amphibian - Hu, Juntao; Ren, Xingyue; Barrett, Rowan; Samma, Eman; Sulkowski, Mikolaj; Brady, Steven (Ecology and Evolution, 2025)
ABSTRACT Phenotypic variation is common across life history and among populations occupying different environments, yet the molecular mechanisms underlying these axes of divergence remain poorly understood. Much work has focused on gene expression as a link between genetic variation, environmental variation, and phenotypes, but post‐transcriptional processes such as alternative splicing—which affect how transcripts are assembled rather than how much of a transcript is produced—are increasingly recognized as additional modulators of plasticity and adaptation. Here, we examined gene expression and alternative splicing together in the wood frog ( Rana sylvatica ), an amphibian with a complex life cycle whose populations differ across replicated gradients of road adjacency and associated pollution. We found extensive transcriptomic differences between hatchlings and adults, with thousands of genes differentially expressed or spliced. Individuals clustered strongly by population for both expression and splicing. Differences at the habitat level were less extensive, but revealed two differentially expressed genes ( HSP70 and Gpsm2 ) and one differentially spliced gene ( Cd82 ) that consistently distinguished roadside and woodland populations. Overall, genetic differentiation between populations was low, suggesting that phenotypic and transcriptomic differences likely emerge in the presence of gene flow and reflect plastic responses. Together, these results highlight transcriptomic plasticity as an important mechanism shaping variation across both development and population differentiation.
Keywords: Alternative splicing; Amphibian; Gene; Gene expression; Genetic variation; Phenotypic plasticity; Population; Transcriptome; alternative splicing; dept.bio; gene expression; local adaptation; maladaptation; population divergence

Freshwater salinization leads to sluggish, bloated frogs and small, cramped embryos but adaptive countergradient variation in eggs - Brady, Steven; Kang, Samantha; Wang, Z.; Layne, Craig; Calsbeek, Ryan (Integrative and Comparative Biology, 2025)
Keywords: Amphibian; Aquatic ecosystem; Biology; Cottus; Ecology; Ecosystem; Freshwater ecosystem; Habitat; Population; Salinity; Soil salinity; dept.bio

Freshwater salinization of seasonal ponds: high salinity and stratification threaten critical, overlooked habitats - Brady, Steven; Benoit, Gaboury (Environmental Science & Technology, 2025)
Keywords: Biology; Critical habitat; Ecology; Environmental science; Fishery; Geology; Habitat; Oceanography; Salinity; Soil salinity; Stratification (seeds); dept; bio; peer-reviewed